THE HISTOPATHOLOGICAL TYPING OF 48 CASES OF ESOPHAGEAL ADENOCARCINOMA AND ITS TISSUE ORIGIN - Huang, Zhizhi; Xie, Fang; Tan, Lijun; Fu, Yuangen (Chinese Journal of Cancer Research, 2013)
Of 2487 cases of esophageal carcinoma pathologiadly conf'mned after resection in 1978--1988 in Shantou, adenocarcinoma accomlted for 1.93% ( 48 cases). These were divided into 6 types; Ordinary well- differentiated adenocarcinoma, I0 cases; Ordinary poorly- differentiated adenocarcinoma, 11 cases; Adeno - squamous carcinoma, 18 cases; Muco - epidermoid carcinoma, 4 cases; "Basal Cell- Like Carcinmna", 4 cases; Cylindronm- Like carcinoma, 1 case. Mucohistochemistry and immunohistochemistry studies revealed some differences among these types; And their prognosis also varied. The tissue origin of these tmnors were discussed.